ANALISIS KEJIWAAN TOKOH UTAMA DALAM NOVEL PENAKLUK BADAI KARYA AGUK IRAWAN MN - Muhammad Dzikrulloh; Onok Yayang Pamungkas; Ari Susanto (RUANG KATA: Journal of Language and Literature Studies, 2022)
This research is a qualitative descriptive study. The approach used is a literary psychology approach. Sources of data obtained from documents. Data collection techniques with library techniques, listen, take notes. The sampling technique used was purposive sampling technique. Data analysis was carried out by interactive data analysis. The validity of the data using theoretical poles. Based on the results of data analysis obtained 3 conclusions. First, the building blocks of the novel are the intrinsic elements. Intrinsic elements include; (a) the major theme is about the struggle for life of a warrior of the nation and religion, minor themes, among others, the problem of matchmaking, the problem of love, the problem of nationalism; (b) the main character is Hasyim Asy'ari, additional characters are Kiai Usman, Kiai Asy'ari, Kiai Ya'qub, Nyai Layinah, Nyai Halimah, Kiai Kholil, Darwis/Ahmad Dahlan, Nafisah, Marto Lemu, Wahab Hasbulloh and Bisri Sansuri; (c) the setting of the place (Tebuireng Islamic Boarding School, Mecca of Saudi Arabia, Rooms, Gedang Islamic Boarding School, Keras Islamic Boarding School, Kademangan Islamic Boarding School, Semarang Land Islamic Boarding School, Siwalan Islamic Boarding School, Ship, Market and Prison), time setting (morning, afternoon, evening, night), background atmosphere (sad, happy, emotional, worried); (d) forward flow; (e) mixed viewpoints; (f) and the mandate that can be taken is honesty. The three values ??of psychological wisdom contained in the novel are (1) religious, (2) honest, (3) tolerance, (4) discipline, (5) hard work, (6) creative, (7) thirst for knowledge, (8) friendly/communicative, (9) nationalism. Keywords: Storm Conqueror, builder element, psychological conflict, psychological wisdom value